The speed of adjustment to demand shocks: A Markov-chain measurement using micro panel data - Christian Müller; Eva Köberl (ETH Zurich, KOF Swiss Economic Institute, 2007)
In this paper we measure the speed at which firms adjust to demand shocks using individual firm data. Identification of shocks is achieved by a combination of quantitative and qualitative judgments on capacity utilisation in micro survey data. A novel feature of our approach is the distinction between positive and negative shocks that allows us to also discriminate between the speed of adjustment following either kind of shock. Furthermore, there is no need for using previous data filtering to extract business cycles or equilibrium definitions but only to observe the states of the firms that define their economic situation. One main result is that the firms' adjustment to these two shocks is varying in speed. It should therefore be paid regard to the separation of positive and negative shocks in empirical and theoretical models. The findings of this paper bear implications for monetary policy making and model building alike.
Keywords: E32; C4; C5; 330; demand shock; Markov-chain; microfoundation; Gesamtwirtschaftliche Nachfrage; Schock; Wirtschaftliche Anpassung; Verarbeitendes Gewerbe; Markovscher Prozess; Schweiz